Influence of meteorological parameters on performance of rainfed cropping systems - KASHYAPI, A. (MAUSAM, 2002)
Rainfall, its distribution along with distribution of temperature. relative humidity (RH), bright sunshine hours (SSH) suggest the possible growing season and crop performance in a given area. Field experiments on five economically feasible, sustainable, rainfed crop sequences viz. fallow (i.e. no crop) – rice-lentil, jute-rice-lentil, direct seeded rice-rice-lentil, mungbean-rice-lentil and sesame-rice-lentil were conducted at Kalyani Farm, W.B., during 1989-91. Mean monthly meteorological parameters viz. rainfall, potential evapotranspiration (PET), SSH, temperature (max. and min.) and RH (at 0700 and 1400 hrs LMT) were obtained from selected agrometeorological observatories (viz. Chinsurah, Haringhata and Barrackpore), adjacent to the Kalyani Farm located in Gangetic alluvial region. The relative yield performance of crops and sequences as influenced by meteorological parameters were studied. In Gangetic alluvial region early rain, moderate to high temperature with high RH during April/May resulted in good pre-kharif crop establishment. Heavy, well distributed precipitation during monsoon months along with moderate temperature and very high RH showed scope for rainfed transplanted kharif rice as the pivot of crop rotation. Kharif rice yields were high especially after jute or mungbean. Profile stored residual moisture along with low rainfall, low temperature and high RH during rabi season resulted in good performance of lentil. Among the five sequences studied, performance of' jute-rice-lentil and mungbean-rice-lentil were the best with sustainable production and net return.